UJI KUALITAS FISIS AIR PADA SUNGAI SALOE KABUPATEN SINJAI - Mahfiah, A Siti; Hernawati, Hernawati; Said L, Muh (JFT : Jurnal Fisika dan Terapannya, 2015)
This research aims to determine the level of water quality in Â Saloe rivers based physical test of color, smell, temperature, taste, conductivity, and total dissolved solids. Sampling was conducted at three sites by measuring the depth of the river and take samples at the surface, middle and bottom of the river. Tests conducted in the laboratory of Chemistry, Faculty of Science and Technology is using descriptive method by measuring the standard measuring tool. From the results of water quality testing at each sampling site, there was information that the water quality of the Saloe rivers can be classified into categories of water quality is good because all the parameters tested still achieve water quality standards based on Government Regulation No. 82 in 2001.